The effect of exaggerated blood pressure response to exercise on exercise on physical working capacity and cardiovascular system function - Venckunas, T.; Poderys, J.; Vainoras, A. (Education. Physical training. Sport, 2000)
The aim of the study was to evaluate the effect of exaggerated blood pressure response to exercise on physical working capacity and cardiovascular system function during exercion in young healthy endurance-trained athletes. We used standart veloergometric stress exercise testing protocol. The results of the study revealed that physical working capacity, diastolic blood pressure and heart rate did not differ in two endurance-trained athletes groups, though heart rate tended to be lower and relative symptom limited exercise capacity (W/kg) was lower in hypertensive group (n=17, exaggerated systolic blood pressure responders, maximal systolic blood pressure values ³220 mmHg) as compared with the control group (n=16, defined as normal systolic blood pressure responders). Although heart rate during testing tended to be lower, double product (systolic blood pressure * heart rate) remained higher, estimated differences between groups were statistically significant (p<0,05) during heavier loads and the first minute of recovery. Two groups were similar in antropometric data, age, specificity of sports activity and training experience. We presume that such a reaction of cardiovascular system function is formed due to inherited inclination to hypertension accompanied with supraoptimal physical loads. Coaches of such sportsmen should be aware that the same external physical loads will lead to different adaptation of the morphology and function of their cardiovascular system as well as physical working capacity.